Performance Evaluation of Small white Common Bean Genotypes in Eastern Amhara, Ethiopia - Genet Kebede Yemer; Eyeberu Abere Bisewur; Mengistu Tefera Yirga; Eshete Wudu Mekonnen; Abay Desale Goshu; Nuru Ahmed Seid; Ambachew Tefera Sisay; Abebe Misiganaw Gedamu; Fentanesh Sendekie Demelash (Universitas Panji Sakti, 2022)
Common bean regional variety trial was carried out at Sirinka, Jari, Cheffa and West belesa (Gondar) from 2017 to 2019 cropping season. The objectives of the trial were to evaluate the performance of genotypes for grain yield and yield related traits and to select and promote the promising ones for verification. Fourteen genotypes including Awash-2 (standard check) were tested using RCBD. Analysis of variance and GGE biplot analysis was employed on multi-environment grain yield data. The combined analysis of variance showed significant differences for both main and interaction effects of genotypes, locations which led to exploit the significant effect of genotype-by-environment interaction. Based on the analysis of variance and GGE biplot analysis, two varieties namely DAB-413 and ZABR 16575-51 F-22 with average grain yield of 2729 kg/ha and 2501 kg/ha, respectively were selected, verified and DAB-413 and have been released for Sirinka, Jari, Cheffa and similar areas in Ethiopia. Therefore, DAB-413 has been recommended for the tested and other similar common bean growing areas to increase production and productivity of this crop.